Study on rural area public attitude toward welfare: employment injury insurance schemes of SOCSO in Sri Aman, Sarawak / Olivia Francesca Sylvester Embuas - Olivia Francesca Sylvester Embuas (Faculty of Business and Management, 2014)
The purpose of this paper is to identify factors influencing public attitude and seeking the relationships of the attitude, knowledge and the media at Sri Aman, Sarawak towards Employment Injury Insurance Schemes. The data was randomly collected from 100 respondents among the people at Sri Aman, Sarawak. The methodology that used by the researcher are population and sampling, data collection method and Statistical Package for Social Science (SPSS) version 20 of data analysis method. The major finding of this study is knowledge have strong relationship with the attitude and vice versa with the media. There are some recommendations for the future researcher. Future researcher should use financial factor as their variable to test whether it affect the public attitude. Furthermore, the researcher should study more about human behavior toward welfare’s schemes. A part from that, researcher might be find the most factors that influence attitude and might be doing research on perception.